A framework for simulation-based engine-control unit inspection in manufacturing phase. (February 2017) - Ham, Won K.; Ko, Minsuk; Park, Sang C.
Abstract: This paper proposes a framework for electronic engine-control unit (ECU) inspection in manufacturing phase. Although various methodologies have been developed for the ECU verification at the development phase, the ECU verification in the manufacturing phase has rarely been brought into focus. ECUs in the manufacturing phase need the verification process in the unified way of the ECU software and hardware components by three major causes: 1) ECU software revision, 2) incomplete installation of software, and 3) quality variation of hardware. For the effective ECU verification in the manufacturing phase, we propose a simulation-based ECU testing methodology. The proposed framework configures virtual vehicle environment to simulate an ECU using a "virtual engine system (VES) model" that specifies the operations of every ECU function during a simulation. The proposed framework employs a reverse engineering approach to identify the operation state transition of an ECU function by reference vehicle states from vehicle experimental data. The main objective of this paper is to design a VES model-based inspection system that simulates an ECU without software modification in brief time for set-up and execution. The proposed framework has been implemented and successfully applied to a Korean automotive company. Highlights: A new simulation-based engine-control unit inspection framework is proposed. The HILS framework in the manufacturing phase is newly developed. For the efficient inspection, the VES (Virtual Engine System) model is devised. The VES model defines ECU operations by vehicle state in test steps. The VES model can be generated via the reverse engineering an ECU.